Peran Unit Billing And Payment Collection Dalam Melakukan Penagihan Piutang Indihome : Studi Kasus Kantor Telkom Regional 1 Sumatera - Diva Mumtazah Putri Zulferry; Nurlaila Nurlaila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Billing and Payment Collection plays an important role at PT. Telekomunikasi Indonesia. This unit is tasked with collecting and handling receivables collection and cash receipts from Indihome customers. The unit's role is to communicate with customers to remind them of their obligations in paying bills for the current month and arrears that are due. This research uses qualitative methods with primary data types. The research results show that the role of the unit greatly influences Telkom's cash income. Telekomunikasi Indonesia, Tbk. However, there are problems faced by both customers and companies, such as network damage, errors in inputting customer data and so on. Therefore, Billing and Payment Collection should provide the right information to customers and must adjust the incoming information in accordance with applicable policies at Telkom so that there are no misunderstandings between marketing and billing, and reduce the level of customer complaints.